KALAH ATAU MENGALAH: INTERAKSI DOMINASI DALAM PERKAWINAN ADAT SUKU BUGIS - Mahmud, M. Amir (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
This study delves into the dynamics of interaction between families in Bugis traditional marriages, with a specific focus on the significance of